Improvement of digital tranformation in training activities for science and technology management employees - Nguyen Thanh Huy; Phung Le Duy; Tran Thanh Thuy; Nguyen Thi Huyen Trang; Pham Thuy Linh; Chu Van Tung; Nguyen Hong Anh; Nguyen Viet Quan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Digital transformation in training activities for science and technology management employees is a key factor to improve capacity and efficiency in the digital economy. This study has investigated, assessed the current situation and identified the impact of digital transformation in training science and technology management employees. Solutions related to technology infrastructure investment; innovation in training programs and methods; enhancement of lecturer capacity; policies to encourage self-learning; international cooperation have been proposed. Those contribute to improve staff capacities, create impacts on the management and development systems of science and technology. Keywords: 25041801